Resource Geography: Utilization of Tongke-Tongke Mangrove Forest Area as A Learning Resource - Syarif, Erman (Universitas Negeri Makassar, 2023)
Learning resources are an important component and have a very important role in improving the quality of learning. The purpose of this study was to determine the activities and learning outcomes of students in resource geography courses by utilizing the tongke-tongke mangrove forest area as a learning resource. This research uses qualitative research methods. The source of data is the resource person (informant). There are three stages of data collection techniques, namely literature study, observation, and interviews. The technical analysis is done through data reduction, data presentation, and conclusion drawing or verification. The results showed that the utilization of tongke-tongke mangrove forest area as a learning resource can optimize student learning activities and outcomes. Utilization of tongke-tongke mangrove forest area as a learning resource can be a solution as a deepening of material and can stimulate student learning motivation in learning activities.